2019
DOI: 10.1186/s12979-019-0156-9
|View full text |Cite
|
Sign up to set email alerts
|

Elevated urine IL-10 concentrations associate with Escherichia coli persistence in older patients susceptible to recurrent urinary tract infections

Abstract: Background Age is a significant risk factor for recurrent urinary tract (rUTI) infections, but the clinical picture is often confused in older patients who also present with asymptomatic bacteriuria (ASB). Yet, how bacteriuria establishes in such patients and the factors underpinning and/or driving symptomatic UTI episodes are still not understood. To explore this further a pilot study was completed in which 30 male and female community based older patients (mean age 75y) presenting clinically wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
1
10
0
1
Order By: Relevance
“…Once her UTI symptoms were resolved, IL-10 expression showed a dramatic decrease ( Figure 2 c). Collectively, these studies and our findings support the pro-inflammatory characteristics and increased expression of IL-10 in inflammatory environments [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Once her UTI symptoms were resolved, IL-10 expression showed a dramatic decrease ( Figure 2 c). Collectively, these studies and our findings support the pro-inflammatory characteristics and increased expression of IL-10 in inflammatory environments [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with the findings in our patient who demonstrated increased levels of IL-10, which correlated with increased levels of IL-8 and TNF-α; these levels decreased when IL-10 expression decreased. Additional studies have revealed that IL-10 is significantly elevated in patients with UTIs [ 35 , 36 ]. Our findings are consistent, since, at the time of our patient’s UTI at the beginning of treatment ( Figure 1 ), she had the highest levels of IL-10 ( Figure 2 c).…”
Section: Discussionmentioning
confidence: 99%
“…The Achtman MLST scheme was used to type the sequenced AnTIC E. coli isolates [18] . PCR-based typing of strains was performed as previously described [19] .…”
Section: Methodsmentioning
confidence: 99%
“…Было показано значимое увеличение концентрации ИЛ-6 и ИЛ-8 у пациентов с ИМП по сравнению с пациентами с ББУ (р < 0,0001). Анализ данных также показал, что у пациентов с рецидивирующей ИМП, у которых отмечалось носительство E. coli, была повышена концентрация противовоспалительного цитокина ИЛ-10 в моче (р = 0,04), что позволило сделать вывод о роли ИЛ-10 в регуляции бактериальной персистенции [39].…”
Section: школа педиатраunclassified